(untitled) - Kay, Ronald D. (Boston, MA, 2004)
This text was developed for the first course in Farm Management, typically taken by a junior/senior level student. It was designed to introduce students to the key concepts on how to effectively manage a farm business. The fifth edition provides students with the basic information needed to measure management performance, financial progress, and the financial condition of the farm business.
Keywords: Farm management,Quản lý nông trại